The Effect Of Problem-Based Learning Model Assisted By Google Sites On Students' Scientific Literacy Skills At Elementary School - Nasution, Abdul Azis; Suyanti, Retno Dwi; Lubis, Wildansyah (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2023)
This study aims to analyze the effect of the Problem-Based Learning model assisted by Google Sites on students' scientific literacy skills by comparing the scientific literacy skills of experimental and control classes at SDN 067251 Medan Deli. This type of research is a quasi-experimental design with Non equivalent Pretest-Posttest Control Group Design. In this study, The population was all fifth-grade students, 40 students in total. The instrument used in this study is a science literacy test. The results showed the sig. (2-tailed) 0.00 < 0.05, it means Problem-Based Learning assisted by Google Sites affects students' scientific literacy skills.Keywords: Problem-Based Leraning, Google Sites, Scientific Literacy.